Pengaruh Pembelajaran Daring dan Locus Of Control Internal Terhadap Motivasi Belajar Mahasiswa Pada Program Studi Pendidikan Ekonomi FKIP Universitas Palangka Raya - Rahman Rahman (FKIP, Universitas Palangka Raya, 2023)
This research aimed at investigating the effect of online learning and Locus of Control Internal to Students learning Motivation in Economic Education Study Program, the Teaching and Education Faculty, Palangka Raya University. The research method used was expos facto in which the source of data were the students of 2019 and 2020 entrance year. The research result showed that the Online learning gave the partial contribution more to the Students lerning motivation as 71,40%, meanwhile Locus of Control internal contributed 17,81%. The analysis of simultaneous testing was done later on and gained the score of Fvalue > Ftable (31,388 > 3,12) with the significance level 0,000 (r < 0,05). The conclusion of this research was 31,388% of Economic Education Study Program students’ learnng motivation affected by Online learning and Locus of Control internal and the rest was affected by other external factors.